Reported Self-care Practices in Pregnancy and Their Relationship With Birth Outcomes in Women Presented to Allied Hospitals of Rawalpindi Medical University - Hafsa Arshad Azam Raja, Haris Mumtaz Malik, Hira Arshad, Aiman Afkar Abbasi, Zaira Azhar, Prof Syed Arshad Sabir (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction Self-care is crucial for promoting health, preventing disease, and maintaining health during pregnancy. Understanding specific healthcare behaviors adopted by women is necessary to improve maternal healthcare delivery and birth outcomes. Objectives This study aimed to assess self-care practices during pregnancy and analyse the relationship between mother self-care and birth outcomes. Materials and Methods A descriptive cross-sectional study was conducted in postnatal wards of gynaecology departments of Allied hospitals of Rawalpindi Medical University from March 2024 to June 2024. Our study population included post-partum primigravida and multigravida women, excluding those having a previous history of comorbidities. For sample size calculation, we used Epi info sample size calculator. Data was collected using a validated self-structured questionnaire. Statistical analysis of data was done using SPSS version 27. Results The study found that 48% of participants had moderately healthy lifestyles, followed by 31.4% with healthy lifestyles, and 20.57% with least healthy lifestyles. Similarly, 57.14% had moderately healthy behaviours, 29.14% had healthy behaviours, and 13.71% had unhealthy behaviours. The relationship between healthy lifestyles and number of pregnancies was significant. PCOS prevalence was higher in participants with moderately healthy or healthy lifestyles. Stillbirths were more prevalent in participants with unhealthy lifestyles. The relationship between pregnancy-induced hypertension, pregnancy-induced diabetes, and healthy behaviours was significant. Conclusion The study suggests that education regarding childbirth is needed, especially for first-time mothers. Healthy lifestyles lead to better birth outcomes.